Youth - Tolstoy, Leo, graf, 1828-1910; Hogarth, C. J. (Charles James), 1869-1942 (Salt Lake City, UT : Project Gutenberg, 2001)
"Youth" by Leo Tolstoy is a semi-autobiographical novel written in the late 19th century. The story is narrated by a young protagonist reflecting on his transition from childhood to adolescence, focusing on his thoughts about morality, self-improvement, and the exuberance and confusion that accompany youth. Central to the narrative are his interactions with friends and family, particularly his mentor Dimitri, who stimulates in him a renewed quest for virtue and a deep introspection about his future. At the start of the novel, the protagonist recounts the beginnings of his youth as he grapples with feelings of inadequacy and self-awareness. He is nearly sixteen and finds himself caught between the influence of his education and the exhilarating undertones of spring that spark dreams of improvement and adventure. The opening also sets up his relationships with significant characters, reflecting on his appearance, inner thoughts, and ambitions to become someone better. He tends to oscillate between lofty ideals, such as engaging in charitable acts, and the stark reality of his mundane life, which often leads him to idle reflections and daydreams. The beginning provides a rich backdrop for his moral struggles and sets the tone for a coming-of-age journey as he navigates the complexities of youth and self-discovery. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Youth_(Tolstoy_novel)
Release date is 2001-05-01
Produced by Martin Adamson, and David Widger
Keywords: Autobiographical fiction; Russia -- Social life and customs -- 1533-1917 -- Fiction; Tolstoy, Leo, graf, 1828-1910 -- Childhood and youth -- Fiction; Russia -- History -- 1801-1917 -- Fiction